PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN LINGKUNGAN KERJA TERHADAP EFEKTIVITAS ORGANISASI - Vivilia Putri Santika; Irma Idayati; Ririn Jeni Yunika; Shalsya Bilbina Atmaja; Cantika Yolanda (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to determine the influence of human resource (HR) competency and the work environment on organizational effectiveness. The method used in this study is a literature review by examining 25 articles from relevant previous research. The results of the study indicate that HR competency has a positive effect on organizational effectiveness, because good competency can improve work ability, decision-making quality, and the achievement of organizational goals. In addition, a conducive work environment also has a positive influence on organizational effectiveness, because it can increase the comfort, motivation, and performance of organizational members. Conversely, low HR competency and an unsupportive work environment can hinder work processes and reduce organizational effectiveness. Overall, increasing organizational effectiveness requires the continuous development of HR competency and the creation of a safe, comfortable, and productivity-supporting work environment.